Safe sex: male–female coalitions and pre-copulatory mate-guarding in a fiddler crab - Milner, Richard N. C. (The Royal Society, 2010)
In fiddler crabs both males and females defend territories that are essential for survival. Given pronounced sexual dimorphism in weaponry, how do weaponless females defend their territory from well-armed males? Using observational data and two simple experiments, we test whether male Uca annulipes protect their female neighbours from conspecific intruders. We show that males defend their female neighbours against male but not female intruders. We also show that females sometimes mate with their immediate neighbours. Male defence of female neighbours appears to represent both pre-copulatory mate-guarding and a territorial coalition. Males who ensure that their neighbour remains female could benefit through increased opportunity for future reproductive success and lower boundary maintenance costs.